Using game theory approach to interpret stable policies for Iran's oil and gas common resources conflicts with Iraq and Qatar - Maryam Esmaeili; Aram Bahrini; Sepideh Shayanrad (Journal of Industrial Engineering International, 2015)
Oil and gas as the non-renewable resources are considered very valuable for the countries with petroleum economics. These resources are not only diffused equally around the world, but also they are common in some places which their neighbors often come into conflicts. Consequently, it is vital for those countries to manage their resource utilization. Lately, game theory was applied in conflict resolution of common resources, such as water, which is a proof of its efficacy and capability. This paper models the conflicts between Iran and its neighbors namely Qatar and Iraq between their oil and gas common resources using game theory approach. In other words, the future of these countries will be introduced and analyzed by some well-known 2 9 2 games to achieve a better perspective of their conflicts. Because of information inadequacy of the players, in addition to Nash Stability, various solution concepts are used based on the foresight, disimprovements, and knowledge of preferences. The results of mathematical models show how the countries could take a reasonable strategy to exploit their common resources.
Keywords: 650; Conflict resolution; Non-cooperative game theory; Oil and gas common resources; Stability definitions